Justifying reimbursement for Alzheimer's diagnostics and treatments: Seeking alignment on evidence. Issue 4 (1st July 2014) - Foster, Norman L.; Hackett, Judith S.M.; White, Greg; Chenevert, Sherri; Svarvar, Patrick; Bain, Lisa; Carrillo, Maria C.
Abstract: The increasing cost of health care combined with expensive new drugs and diagnostics is leading to more frequent gaps between regulatory and subsequent reimbursement approval decisions. As a result, persons with Alzheimer's disease may have difficulty accessing the benefit of medical advances. In contrast to the long history and established structure for drug approval, payer decision making is dispersed, not standardized, and perspectives on necessary evidence and the evaluation of this evidence differ and are often poorly defined. Particularly challenging is how to demonstrate the value of drugs and diagnostics for patients who do not yet have significant functional decline. Although discussions to develop consensus continue, clinical trials should begin to incorporate health system and patient‐oriented outcomes. In some situations, additional studies designed to demonstrate value and comparative effectiveness will be needed. Such studies should examine outcomes of representative populations in community settings. To assure scientific advances in diagnosis and treatment benefit in patients, developing evidence to support reimbursement will become as important as obtaining regulatory approval.